In vivo fluorescence microscopy of corneal neovascularization - Becker, Matthias D.; Kruse, Friedrich E.; Joussen, Antonia J. M.; Rohrschneider, Klaus; Nobiling, Rainer; Gebhard, Martha-Maria; Völcker, Hans Eberhard (Graefe's archive for clinical and experimental ophthalmology, 1998)
· Purpose: The purpose of our study was to establish an animal model to study the microcirculation in corneal neovascularization in the living animal atraumatically. · Methods: Corneal neovascularization was induced in New Zealand white rabbits by a standard micropocket assay utilizing pellets with 250 ng basic fibroblast growth factor. Anesthesia consisted of intramuscular injections of ketamine and xylazine. Intravital microscopy was performed without preparation of the cornea. Rhodamine 6G was used as fluorescent dye to stain leukocytes. Fluorescein-isothiocyanate-dextran served as plasma marker. Microcirculation analysis was done off-line by digital video imaging with special analysis software and included the following parameters: vessel diameters, blood velocity, and differentiation of leukocytes according to their interaction with endothelium into free-floating, rolling and sticking leukocytes. · Results: Vessel diameters in venular trunk vessels showed diameters of 54.0 ± 13.3 μm with 1.1 ± 0.5 mm/s flow; 29.4 ± 16.3% of all leukocytes were attached to the vascular wall. The number of sticking leukocytes was found to be 17.8 ± 36.0 cells/mm2 endothelial surface. Values are given for arteriolar trunk and branch as well as venular branch vessels. · Conclusions: This method for in vivo microscopic observation and quantification of the vasculature of the ocular surface seems to be suitable for evaluation of microhemodynamic and leukocyte measurements in mature neovascular vessels. It allows atraumatic experiments without corneal preparation procedures which disturb the microcirculation. The results concerning microhemodynamics and adherence of leukocytes are in a range comparable to other microcirculation studies. This new model could provide insight into the pathophysiology of microcirculatory disorders of the anterior eye segment, e.g. during angiogenesis.
Gesehen am 10.03.2025